2018
DOI: 10.1080/01480545.2018.1504961
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin protects microglia against rotenone-induced toxicity in a hormetic manner through targeting oxidative stress response, genes associated with Parkinson’s disease and inflammatory pathways

Abstract: Rotenone, an environmental toxin, triggers Parkinson's disease (PD)-like pathology through microglia-mediated neuronal death. The effects and molecular mechanisms of flavonoid luteolin against rotenone-induced toxicity was assessed in microglial BV2 cells. Cells were pretreated with luteolin (1-50 µM) for 12 h and then was co-treated with 20 µM of rotenone for an additional 12 h in the presence of luteolin. The viability (MTT), IL-1β and TNF-α levels and lactate dehydrogenase (LDH) release (ELISA), and Park2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Mn also increased LRRK2 expression in both macrophages and microglia, indicating that Mn may enhance LRRK2 at the transcriptional level. Interestingly, another toxicant, rotenone, also increased LRRK2 expression in microglia [62].…”
Section: Discussionmentioning
confidence: 99%
“…Mn also increased LRRK2 expression in both macrophages and microglia, indicating that Mn may enhance LRRK2 at the transcriptional level. Interestingly, another toxicant, rotenone, also increased LRRK2 expression in microglia [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, neobaicalein pre-treatment survived the rotenone treated cells significantly and decreased the rate of early apoptosis, as well as late apoptosis/necrosis. Other flavonoids with a similar structure as neobaicalein have also been shown the potential against rotenone toxicity, suggesting the neuroprotective effects of flavonoids [9,60,61]. In addition to cell death, another reason, which can explain the symptoms of PD, is the disability of neurons in recruiting transmitters, synaptic communication with neighbor neurons, and glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Wen et al reported that the overexpression of miR-185 gene can lead to the inhibition on apoptosis of dopaminergic neurons through regulating the mTOR-dependent autophagy pathway [25]. Furthermore, Elmazoglu et al reported a decrease in the PARK2 gene expression level in an in vitro model of PD induced by rotenone [26]. The increase in the PARK2 gene expression level was also observed in clinical cases of PD or PD models occurred through certain epigenetic processes.…”
Section: Discussionmentioning
confidence: 99%